Social behaviors as welfare indicators in teleost fish - Cavallino, Luciano; Rincón, Laura; Scaia, María Florencia (Frontiers in Veterinary Science, 2023)
Animal welfare is a key issue not only for aquaculture industry and food production, but also for daily husbandry practices in research topics related to physiology in wild and farmed animals. In this context, teleost fish constitute interesting models to assess alternative welfare indicators because of their wide diversity in reproductive and social structures. Any framework for assessing teleost fish welfare needs to account for the physiological mechanisms involved in each species as a first step. A comprehensive approach should also take into account how these physiological and behavioral parameters can be altered by environmental enrichment considering the specific requirements in each case and identifying intrinsic biological characteristics of individual species. This review will show how cortisol and sex steroids regulate social behavior in teleost fish, and how different aspects of social behavior can be employed as welfare indicators according to specific characteristics in each case. This article will consider evidence in teleost fish, including cichlids, characids and cyprinids with different reproductive strategies and social structures (e.g. territorial social hierarchies or shoaling behavior). Neotropical species will be particularly emphasized. The main laboratory-based animal welfare indicators are cortisol, a classical stress hormone, together with sex steroids. Considering that the endocrine landscape is intrinsically related to social behavior, reproductive and agonistic behavioral traits such as aggression, anxiety and courtship are key elements to assess welfare under housing and culture conditions. This review highlights the importance of assessing physiological mechanisms and identifying behavioral characteristics in teleost fish, especially in Neotropical species, as a baseline to understand which environmental enrichment can improve animal welfare in each individual species.